Nutritive and Antioxidant properties of Shade Dried Leafy Vegetables Consumed in Northern Côte d‘Ivoire - Oulaï, Patricia Dehegnan; Zoue, Lessoy Yves Thierry; Niamké, Sébastien Lamine (Turkish Journal of Agriculture - Food Science and Technology, 2016)
Leafy vegetables are highly perishable and often subjected to post-harvest wastes. Among the various methods of preservation, the effect of shadow drying on the nutritive value and antioxidant properties of five (5) leafy vegetables species widely consumed in Northern Côte d‘Ivoire was investigated. These species were Amaranthus hybridus, Andasonia digitata, Ceiba patendra, Hibiscus sabdariffa and Vigna unguiculata. Experiment was conducted as follow: portions of washed and drained fresh leafy vegetables (500 g) were spread on clean filter paper and kept in a well-ventilated room of the laboratory at 25Â°C for 5, 10 and 15 days. The results of proximate composition after 15 days of shadow drying were: moisture (15.19 – 20.36%), ash (9.14 -19.54%), crude fiber (11.04 – 27.40%), proteins (11.14 - 17.94%), lipids (2.41 – 5.86%) and carbohydrates (16.59 – 45.14%). The concentration of minerals increased with respective values after 15 days of shadow drying: calcium (68.14-408.09 mg/100 g), magnesium (50.62-317.23 mg/100 g), iron (27.52-92.03 mg/100 g) and zinc (10.17-16.73 mg/100 g). During shadow drying, vitamin C and carotenoids were subjected to losses estimated to 35.52 – 70.50% and 22.82 – 45.63%, respectively. Contrary to these losses, antioxidant activity increased and ranged from 57.45 to 75.55 % after 15 days of shadow drying. All these results suggest that the considerable nutrient contents of shade dried leafy vegetables make them good source of food supplements in order to meet the nutritional requirements of Ivorian population.